Tinjauan Perancangan Tracer (Outguide) Pada Unit Penyimpanan Rekam Medis Di RSU Imelda Pekerja Indonesia Tahun 2022 - Siddik Karo-Karo; Marjones Hardy H. Sihombing (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda, 2023)
Tracer (outguide) is a substitute for medical records that will be removed from storage for any purpose. A good tracer should be made of strong and colorful materials. The function of the tracer is to show where medical record documents are when they are not in storage. Tracers can also improve efficiency and accuracy by showing where medical records are stored when they return. The purpose of this study was to redesign the tracer at Imelda Workers' Hospital in Indonesia by replacing materials, shapes, and designs to make it easier for officers to carry out their duties, namely inserting tracers into the shelves between the densely packed medical record files. The research method used is descriptive qualitative research. And the research instruments used are interview guidelines and observation check lists. The tracer (outguide) at Imelda Workers' Hospital in Indonesia has not been used for about a year because all tracers (outguides) have been damaged. The tracer (outguide) was damaged because the material was too stiff and broke easily when the officer inserted the tracer into the storage rack between the dense medical record files. RSU Imelda Workers Indonesia requires a tracer (outguide) made of strong, durable, not easily damaged, torn, broken and researchers have redesigned the tracer (outguide) as the results in the design above, namely by using flexible mica plastic material with a thickness of 0.70 mm , and the color chosen by the researcher in this design is black. The shape and size of the tracer (outguide) in this design is the same as the shape and size of the previous tracer (outguide) in Imelda Workers' Hospital in Indonesia. medical devices with new materials and designs such as the results in this design.